Synthesis of CuO, ZnO and SnO2 Coupled TiO2 Photocatalyst Particles for Enhanced Photodegradation of Rhodamine B Dye - Amna Jwad Kadem; Zhuang Min Tan; Nanthini Mohana Suntharam; Swee-Yong Pung; Sivakumar Ramakrishnan (Bulletin of Chemical Reaction Engineering & Catalysis, 2023)
Environmental pollution is a global problem and dye pollution is one of the major factors. TiO2 shows promising photocatalytic properties that can degrade organic pollutants such as dye under ultraviolet (UV) irradiation. However, TiO2 possesses some disadvantages such as a wide band gap and a high recombination rate of electron-hole pairs. Coupling TiO2 with various metal oxides can enhance photocatalytic properties. In this work, photodepositon (reduction of metal ions on TiO2) followed by the thermal oxidation method were used for the coupling of TiO2 with CuO, ZnO, or SnO2 under various methanol concentrations (25 vol% or 50 vol%) and deposition duration (1 h or 3 h) to observe the effect of these parameters on the photocatalytic degradation activity on Rhodamine B (RhB) dye (up to 90 min). The rate constant of the photodegradation reaction (k) has improved from 0.0141 min−1 (uncoupled TiO2) to 0.0151~0.0368 min−1. Overall, CuO/TiO2 and SnO2/TiO2 samples have shown similar photocatalytic properties (average rate constants of 0.0341 min−1 and 0.0327 min-1, respectively), and both performed better than ZnO/TiO2 in terms of RhB photodegradation (average rate constants of 0.0197 min−1). The difference in photocatalytic performance can be explained by the bandgap of metal oxides and their relative band positions with TiO2. Lastly, CuO/TiO2 (50 vol%, 3 h) and SnO2/TiO2 (50 vol%, 3 h) have shown the best photocatalytic properties respectively due to a longer deposition time and higher concentration methanol, resulting in more deposited materials. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).